Utilization of growth monitoring and promotion services among children younger than 2 years in West Armachiho district, Northwest Ethiopia - Novel Teklemuz; Mekonnen Sisay; Lemlem Daniel Baffa; Berhanu Mengistu; Azeb Atenafu (Frontiers Media S.A., 2023)
IntroductionInadequate physical growth and poor development of children are prevalent and significant problems worldwide, with 149 million children younger than 5 years stunted and 49 million wasted. Growth monitoring and promotion (GMP) is one of the major activities implemented with the aim of capturing growth faltering before the child reaches the status of undernutrition. In relation to this, the Amhara region, where the study area is found, is a highly burdened area for child malnutrition. Thus, it needs further investigation about the utilization of GMP services and associated factors among children younger than 2 years in the study area.ObjectiveThe aim of this study was to assess the utilization of growth monitoring and promotion services and associated factors among children younger than 2 years.MethodsA community-based cross-sectional study was conducted in the West Armachiho district, including 703 mother-child pairs, with a response rate of 94.7%. A simple random sampling technique was used to select the respondents. Both bivariable and multivariable logistic regression analyzes were performed. An adjusted odds ratio (AOR) with a 95% confidence interval was used to measure the strength of the association.ResultsThe proportion of utilization of growth monitoring and promotion services in the West Armachiho district was 13.7% (95%Cl; 11.2, 16.4). Factors such as maternal educational status (AOR = 2.17, 95%Cl; 1.05, 4.49), institutional delivery (AOR = 3.16, 95%Cl; 1.62, 6.13), family size (AOR = 2.66, 95%Cl; 1.13, 6.23), access to health facility (AOR = 3.17, 95%Cl; 1.45, 6.95), and maternal knowledge (AOR = 4.53, 95%Cl; 2.71, 7.59) were significantly associated with the utilization of growth monitoring and promotion services.ConclusionUtilization of growth monitoring and promotion services in children younger than 2 years in the West Armachiho district was low. Thus, giving due attention to the improvement of the knowledge of the mothers/caregivers about child GMP services and counseling them about the importance of facility delivery is vital to improving growth monitoring and promotion services in the area.